2009
DOI: 10.1111/j.1349-7006.2009.01160.x
|View full text |Cite
|
Sign up to set email alerts
|

Shear stress induces internalization of E‐cadherin and invasiveness in metastatic oesophageal cancer cells by a Src‐dependent pathway

Abstract: Metastatic disease is dependent on tumor cell migration through the venous and lymphatic systems and requires dynamic rearrangement of adherens junctions. Endocytosis of cadherins is a key mechanism to dynamically arrange adherens junctions, signaling, and motility in tumor cells; however, the role of shear in regulating this process in metastatic cells is unknown. In this study, the role of shear in regulating cell surface expression of E-cadherin was investigated. M etastatic cell survival is dependent on ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 28 publications
(52 reference statements)
1
34
0
Order By: Relevance
“…One recent study found that a non-junctional, presumably internalized, E-cadherin expression pattern was associated with poor survival in nasopharyngeal cancer (Xie et al, 2010). Another found Src-dependent E-cadherin internalization with shear stress in an oropharyngeal cancer cell line (Lawler et al, 2009). Increased E-cadherin internalization has also been found in a mouse model of UV-irradiation-induced squamous cell carcinoma (Brouxhon et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…One recent study found that a non-junctional, presumably internalized, E-cadherin expression pattern was associated with poor survival in nasopharyngeal cancer (Xie et al, 2010). Another found Src-dependent E-cadherin internalization with shear stress in an oropharyngeal cancer cell line (Lawler et al, 2009). Increased E-cadherin internalization has also been found in a mouse model of UV-irradiation-induced squamous cell carcinoma (Brouxhon et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…As part of a mechanosensory protein complex, Src mediates the cellular response to mechanical stimuli in numerous non-chondrocytic cell types (23,37). In particular, Chaturvedi et al (14,15) have shown that, in the study of proliferation and migration of human Caco-2 intestinal epithelial cells mediated by rhythmic mechanical deformation, Src is a proximal kinase in the regulation of both proliferation and migration.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, evidence suggests that low levels of shear stress, typical of the venous system, may have opposite effects on intracellular signalling and tumour cell function. For example, venous shear stress has been suggested to induce an EMT, as shown by the shear-mediated internalization of E-cadherin in metastatic oesophageal OC-1 tumour cells 115 . Moreover, exposure of free-flowing OC-1 cells to a shear rate of 200 s −1 increased their mobility and invasive capacity in vitro 115 .…”
Section: Extravasation Of Circulating Tumour Cellsmentioning
confidence: 99%